Teacher Role Analysis In Developing Communication And Collaboration Capabilities On Elementary Education Level - Nurmalisa, Yunisca; Seftriyana, Elisa (Efektor, 2019)
The purpose of this study was to analyze the role of the teacher in developing the ability to communicate and collaborate at the elementary school level in East Pringsewu. This study use a qualitative method by grounded theory design. Data analysis use interactive analysis by data reduction, data presentation, and data verification steps. The data credibility test uses techniques triangulation and source triangulation. The results of the study illustrated that teachers had a role that has not been effective in providing the ability to communicate and collaborate according to the demands of 21st century competence. The role of teachers in the 21st century has not been able to provide functional relationships that are able to construct, motivate, and track students' minds. The professional role of teachers that need to be developed can encourages learners to exchange ideas and provide verbal reinforcement related to their needs in carrying out communication and collaboration.